Eficiência energética em edificações residenciais sob a ótica do RTQ-R na cidade de Várzea Grande - MT : um estudo de caso - Freire, Emilly Marques Silva (2014)
Due to the continuous increase in the consumption of electric energy in Brazil, increasing it becomes a concern for rational and efficient use of energy in all sectors, particularly in the residential sector. In this context, this work aims at assessing the level of energy efficiency in a housing unit of Social Interest (HIS) located in Várzea Grande - MT, which presents the conventional building system, with brick walls and clay tile. For assessing the energy efficiency level of housing used the Technical Regulation for the Quality Level of Efficiency in Residential Buildings (RTQ-R) through the prescriptive method and computer simulation. It was found that based on prescriptive calculation, the housing unit received D level of efficiency, due to the mismatch of the thermal transmittance and thermal capacity of the walls and thermal transmittance of the roof that had values above and below that recommended by the regulation , respectively. The method by computer simulation, the result showed the same level of efficiency for housing. After evaluating the level of efficiency , we analyzed all the variables contained in the equation of prescriptive regulation (RTQ-R), which showed the highest coefficients of variation in the results of degree- hour were : Upar, CTalta, α ( walls and roofs ) , and Fvent Somb. From the proposal to improve the building, housing unit received A-level energy efficiency. That with this work, the Regulation and its application can be broadcast in the city of Grande Floodplain demonstrating its effectiveness and helping to improve the efficiency of buildings in the residential sector is expected.